Ever Use of E-Cigarettes Among Adults in the United States: A Cross-Sectional Study of Sociodemographic Factors - Sericea Stallings-Smith DrPH; Taylor Ballantyne BSH (SAGE Publishing, 2019)
E-cigarette use among adolescents is well-documented, but less is known about adult users of e-cigarettes. The purpose of this study was to examine associations between sociodemographic factors and e-cigarette use in a nationally representative sample of adults in the United States. Cross-sectional data from the National Health and Nutrition Examination Survey (NHANES) for years 2015-2016 were analyzed to assess e-cigarette use among 5989 adults aged ≥18 years. Multivariable logistic regression was conducted to examine associations between the sociodemographic exposures of age, sex, race, marital status, education level, employment status, and poverty-income ratio and the outcome of e-cigarette use. The weighted prevalence of ever use of e-cigarettes was 20%. Compared with adults aged ≥55 years, odds of e-cigarette use were 4.77 times (95% confidence interval [CI] = 3.63-6.27) higher among ages 18 to 34 years and 2.16 times (95% CI = 1.49-3.14) higher among ages 35 to 54 years. Higher odds of e-cigarette use were observed among widowed/divorced/separated participants compared with those who were married/living with a partner, among participants with less than high school (odds ratio [OR] = 1.47; 95% CI = 1.08-2.00) or high school/general educational development (GED) education (OR=1.41; 95% CI = 1.12-1.77) compared with those with college degrees/some college, and among those with incomes below the poverty level (OR=1.31; 95% CI = 1.01-1.69) compared with above the poverty level. For non-smokers of conventional cigarettes, higher odds of e-cigarette use were observed among males compared with females, Mexican Americans/Other Hispanics compared with non-Hispanic whites, and non-working participants compared with those who were working. Overall findings indicate that individuals who are widowed/divorced/separated, individuals with lower education, and with incomes below the poverty level are likely to report ever use of e-cigarettes. As increasing evidence demonstrates negative health consequences, e-cigarette initiation may ultimately contribute to additional smoking-related health inequalities even among non-smokers of conventional cigarettes.